A computational study of the double hysteresis phenomenon during reactive sputtering. (1st September 2022) - Van Bever, J; Strijckmans, K; Depla, D
Abstract: When process parameters such as the reactive gas partial pressure or the discharge voltage are studied as a function of the reactive gas flow during reactive magnetron sputtering, the obtained curve has an S-shape. A direct consequence of this behaviour is that process control based on the reactive gas flow exhibits hysteresis. Under specific conditions, it is possible to observe two S-shaped curves: one when the reactive gas pressure is increased, the other during the return to the initial state by decreasing the reactive gas pressure. This behaviour has been described as double hysteresis behaviour. The origin of the double hysteresis behaviour is computationally studied by high-throughput calculations using a previously developed model. The influence of different process and material parameters were evaluated based on newly developed measures to characterize the calculated process curves. This high-throughput analysis reveals that the double hysteresis behaviour is linked to the difference in the removal rate of non-reacted implanted ions during the increase and decrease of the reactive gas pressure. Within the parameter space a region can be defined for which the double hysteresis behaviour is strong. The latter can not only assist further experiments to study this behaviour but also defines conditions to limit its impact. For Al, a discharge current density of approximately 0.025 A cm −2 was found to maximize double hysteresis.